Boundary friction on molecular lubricants: rolling mode? - Loktev, V.M.; Pogorelov, Yu.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
A theoretical model is proposed for low-temperature friction between two smooth rigid solid surfaces separated by lubricant molecules, admitting their deformations and rotations. The appearance of different modes of energy dissipation (by «rocking» or «rolling» of lubricants) at slow relative displacement of the surfaces is shown to be accompanied by stick-and-slip features and reveals a nonmonotonic (mean) friction force vs external load.